Boundary Trace Operator in a Domain of Hilbert Space and the Characteristic Property of its Kernel - Bogdanskii, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We prove an infinite-dimensional analog of the classical theorem on density of the set $C_0^1 (G)$ of finite smooth functions in the kernel of the boundary trace operator $γ: H_1(G) → L_2(∂G)$.